KONDISI HUTAN BAKAU TEBANGAN MASYARAKAT DAN INDUSTRI PULP DI BATU AMPAR KALIMANTAN BARAT - Djohan, Tjut Sugandawaty; Laksono, P.M.; Anantasari, Esti; Utama, Angga N.; Suhesthiningsih, Krisni (Jurnal Kawistara, 2015)
The purpose of this research was to study tree cutting of mangrove forest by the local people of Batu Ampar and the pulp industry at Kapuas river estuary. At each site the rapid measurement methods were established using quadrate plots of 20m x 20m and 5m x 5m, each with 2 replicates. The results revealed that the local people only cut the selective trees of Rhizophora apiculata and Bruguiera gymnorhiza with diameter of 20-25 cm2 at 0.25 ha wide, which created gap canopy as small disturbace to the mangrove forest. This area of gap canopy immediately was colonized and dominated by R. apiculata. The mangrove tree cuttings created the phase gap generations. This forest recovered quickly, thus the small distrurbance maintained the mangrove tree species diversity. The Rhizophora roots were habitat for nusery grown of larval shrimps, crabs, and fishes. The pulp industry cut all of the mangrove species wich created big disturbance and huge gap area. The forest also recovered quickly, but was dominated by Xylocarpus granatum. Thus, the big disturbance by the pulp industry caused the shifted species of the mangrove forest species from Rhizophora and Bruguiera to Xylocarpus. The roots of Xylocarpus tree were not habitat forthelarval shrimps, crabs, and fishes, which decreased the fisherman catch. The forest rehabilitation of industrial cutting was planted regularly with Rhizophora, and created many current canals which proned to the erosion. Thus the pulp industry of mangrove forest cutting threatened nursery habitat and species diversity at the mangrove forest of Batu Ampar.